NICE on antimicrobial prescribing for leg ulcer infection. Issue 7 (4th September 2020) - Chaplin, Steve
Abstract : NICE's antimicrobial prescribing guidelines offer evidence‐based advice to help health professionals and patients manage common infections and reduce antimicrobial resistance. This article summarises the antimicrobial guideline on managing leg ulcer infection (NG152).